2013
DOI: 10.1111/ajt.12426
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of Urinary CXCL9 as a Risk-Stratifying Biomarker for Kidney Transplant Injury

Abstract: Noninvasive biomarkers are needed to assess immune risk and ultimately guide therapeutic decision-making following kidney transplantation. A requisite step toward these goals is validation of markers that diagnose and/or predict relevant transplant endpoints. The Clinical Trials in Organ Transplantation-01 protocol is a multicenter observational study of biomarkers in 280 adult and pediatric first kidney transplant recipients. We compared and validated urinary mRNAs and proteins as biomarkers to diagnose biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
220
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(242 citation statements)
references
References 31 publications
20
220
0
2
Order By: Relevance
“…Low urinary CXCL9 was the best predictor of longterm kidney graft stability (319). In renal transplants with delayed graft function, early expression of RANTES with the consecutive invasion of CCR1-positive cells was associated with subsequent renal fibrosis, tubular atrophy and worse renal allograft outcome (320).…”
Section: Chemokines and Innate Immunitymentioning
confidence: 99%
“…Low urinary CXCL9 was the best predictor of longterm kidney graft stability (319). In renal transplants with delayed graft function, early expression of RANTES with the consecutive invasion of CCR1-positive cells was associated with subsequent renal fibrosis, tubular atrophy and worse renal allograft outcome (320).…”
Section: Chemokines and Innate Immunitymentioning
confidence: 99%
“…Suthanthiran et al 2 recently showed that the urinary cell mRNA profile can serve as a diagnostic and prognostic biomarker of TCMR. Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells.…”
mentioning
confidence: 99%
“…10 A recent multicenter observational trial in 280 patients with kidney transplants reported that the CXCL9 protein level had a strong predictive value for noninvasively diagnosing TCMR. 5 Although there have been improvements in diagnosing TCMR using these new methods, it is noteworthy that, at the same time, the clinical presentation of renal allograft rejection has changed dramatically, with the incidence of TCMR progressively decreasing to 10%-15% using tacrolimus-based immunosuppression. For example, in the clinical trials in organ transplantation 4 (CTOT-4) Study, only 36 of 385 patients (9.3%) developed TCMR at 1 year post-transplant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, urinary CXCL‐10 mRNA has been shown to be elevated up to 6 to 7 days prior to an acute rejection episode 7. In a recent prospective multicenter study, urinary mRNA of CXCL‐9 (as well as urinary CXCL‐9 protein) was shown to be predictive for the presence of acute rejection 8.…”
Section: Mrnas In Urine As Biomarkers Of Graft Performancementioning
confidence: 99%